A case of ulcerative colitis complicated with bronchiolitis obliterans organizing pneumonia (BOOP) and air leak syndrome - Müge AYDOĞDU; Gül GÜRSEL; Ezgi ÖZYILMAZ; Nalan AKYÜREK; Leyla MEMİŞ (Turkish Journal of Gastroenterology, 2019)
-